C reactive protein for risk stratification in acute coronary syndromes? Verdict: unproven. Issue 11 (31st October 2003) - Kennon, S; Timmis, A D; Whitbourn, R; Knight, C
Abstract : Although C reactive protein is intimately involved with the pathogenic mechanisms that drive acute coronary syndromes, there is no evidence that it is helpful for identifying patient groups who might benefit from particular treatment strategies